Penerapan Terapi Ankle Pump Exercise Dengan Elevasi Kaki 30 Derajat terhadap Derajat Edema pada Pasien Gagal Ginjal Kronik di Rs Roemani Muhammadiyah Semarang - Siti Kurniatun; Rahayu Winarti (Journal of Medical Practice and Research, 2026)
Chronic kidney disease is frequently associated with fluid imbalance leading to peripheral edema, which negatively affects patient comfort and functional capacity. This study aimed to evaluate the effectiveness of ankle pump exercise combined with 30° leg elevation in reducing edema severity among patients undergoing hemodialysis. An empirical case study design with a one group pretest–posttest approach was applied to five patients diagnosed with chronic kidney disease and lower extremity edema at Roemani Muhammadiyah Hospital, Semarang. Data were collected through structured clinical observation using standardized edema grading before and after a three-day intervention protocol consisting of dorsiflexion and plantarflexion movements followed by leg elevation. The findings demonstrated a consistent reduction in edema degree across all participants, with clinical improvement observed both in measurement scale and categorical severity. The results suggest that the intervention facilitates venous return and reduces interstitial fluid accumulation through mechanical and gravitational mechanisms. This study highlights the clinical relevance of simple, non-pharmacological interventions as supportive strategies in managing edema among chronic kidney disease patients.